Peran Pancasila Dalam Penegakan Hukum Di Indonesia - Riyansyah, Muhammad (Philosophiamundi, 2025)
This study examines the role of Pancasila as the philosophical foundation and guiding paradigm of law enforcement in Indonesia. Historically, Pancasila evolved from value concepts rooted in Sanskrit tradition to its establishment as the state ideology embodying principles of morality, ethics, and humanism that orient national governance. In the legal domain, Pancasila functions not only as a fundamental norm but also as a source of values that must be reflected in the formulation of legislation, the implementation of law, and judicial decision-making. Using a normative legal research method, this study finds that law enforcement in Indonesia is inseparable from efforts to realize substantive justice grounded in the values of divinity, humanity, unity, democracy, and social justice. Judges play a pivotal role because they possess the authority to interpret and apply the law in response to evolving social dynamics. However, this judicial discretion must remain within the philosophical and constitutional boundaries of Pancasila and the 1945 Constitution to ensure that judicial decisions uphold legal certainty while also reflecting public morality and civilized justice. The findings underscore that revitalizing Pancasila’s values across all stages of law enforcement is essential for developing a responsive legal system that prioritizes justice and aligns with Indonesia’s cultural character.